Elastic Lattice and Excess Charge Carrier Manipulation in 1D–3D Perovskite Solar Cells for Exceptionally Long‐Term Operational Stability. Issue 48 (24th September 2021) - Zhan, Yu; Yang, Fu; Chen, Weijie; Chen, Haiyang; Shen, Yunxiu; Li, Yaowen; Li, Yongfang
Abstract: 3D organic–inorganic hybrid halide perovskite solar cells (pero‐SCs) inherently face severe instability issue due to ion migration under operational conditions. This ion migration inevitably results from the decomposition of ionic bonds under lattice strain and is accelerated by the existence of excess charge carriers. In this study, a 1D–3D mixed‐dimensional perovskite material is explored by adding an organic salt with a bulk benzimidazole cation (Bn + ). The Bn + can induce 3D perovskite crystalline growth with the preferred orientation and form a 1D BnPbI3 perovskite spatially distributed in the 3D perovskite film. For the first time, the electro‐strictive response, which has a significant influence on the lattice strain under an electric field, is observed in polycrystalline perovskite. The 1D–3D perovskite can effectively suppress electro‐strictive responses and unbalanced charge carrier extraction, providing an intrinsically stable lattice with enhanced ionic bonds and fewer excess charge carriers. As a result, the ion migration behavior of the p‐i‐n 1D–3D based pero‐SC is dramatically suppressed under operational conditions, showing ultra‐long‐term stability that retains 95.3% of its initial power conversion efficiency (PCE) under operation for 3072 h, and simultaneously achieving an excellent PCE with a hysteresis‐free photovoltaic behavior. Abstract : Electro‐strictive strain in 3D polycrystalline perovskite is observed, which can lead to an accelerated ion migration under operational conditions. The 1D–3D perovskite, that is, 1D BnPbI3 perovskite, spatially distributed in the 3D perovskite film and compensating the dangling bonds in the grain boundaries, can effectively inhibit electro‐strictive responses and unbalanced charge carrier extraction, realizing ultralong operational stability.